Chemical Characteristics and Antioxidant Content Properties of Cold Pressed Seed Oil of Wild Milk Thistle Plant Grown in Jordan - Dabbour, I.R.; Al-Ismail, K.M.; Takruri, H.R.; Azzeh, F.S. (Pakistan Journal of Nutrition, 2014)
This study aimed to examine the chemical characteristics and antioxidant content properties of cold-pressed milk thistle seed oil. Acidity and peroxide value were determined by chemical standard titration method and oxidative stability index was determined by Rancimate. Using GLC, fatty acid composition, phytosterols and squalene were measured. While, alpha-tocopherol content was determined by HPLC. The total phenolic content, radical-scavenging capacity and total antioxidant capacity were determined spectrophotometrically. The chemical characteristics of cold-pressed oil were as follows: acidity (0.64%), peroxide value (0.34 meq O2/kg of oil), oxidative stability index (55.7 and 12.9 h at 80 and 100°C, respectively), fatty acid composition (19.5, 22.9 and 57.6% for SAT, MUFA and PUFA, respectively), phytosterol (2520 mg/kg), squalene (9.35 mg/kg), alpha-tocopherol content (237.4 mg/kg), total phenolic content (1.16 mg GAE/g oil), radical-scavenging capacity against stable DPPH radical (IC50 = 3.34 mg/mL) and total antioxidant capacity (2.29 mmol/L). These data suggest that cold-pressed milk thistle seed oil may serve as dietary source of high PUFA and MUFA, phytosterols, phenolic compounds and natural antioxidants and can be a remarkable candidate for use in healthy food preparations mixed with other vegetable oils or alone.